1991
DOI: 10.1111/j.1365-2621.1991.tb08623.x
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Spectroscopy Determination of Physical and Chemical Characteristics in Beef Cuts

Abstract: The qualities of beef cuts were compared with near-infrared (NIR) spectroscopy readings using reflectance, transmittance and a fiber optic probe. Multiple linear regression analyses were used to select the optimum wavelengths for estimating beef properties. High multiple correlation coefficients (R) were obtained for Warner-Bratzler shear value (R=0.798-0.826), protein (R=0.822-0.904), moisture (R = 0.895-0.941), fat (R = 0.890-0.965) and energy content (R=0.899-0.961) with each reflectance, transmittance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 11 publications
4
60
1
2
Order By: Relevance
“…Near infrared spectroscopy has been explored by many groups as a potential tool for providing an objective evaluation of meat sensory attributes (Mitsumoto, Maeda et al 1991;Park, Chen et al 1998;Rodbotten, Mevik et al 2001;Venel, Mullen et al 2001;Liu, Lyon et al 2003). However, although these studies indicated that NIR spectroscopy is feasible and promising in the quality control of meat products, the results, especially on meat tenderness predictions, have been inconsistent, partially because NIR spectroscopy measures the overtones of fundamental molecular vibration modes which are often overlapped to yield broad bands that do not provide high resolution information about the biochemical landscape of the meat.…”
Section: Introductionmentioning
confidence: 99%
“…Near infrared spectroscopy has been explored by many groups as a potential tool for providing an objective evaluation of meat sensory attributes (Mitsumoto, Maeda et al 1991;Park, Chen et al 1998;Rodbotten, Mevik et al 2001;Venel, Mullen et al 2001;Liu, Lyon et al 2003). However, although these studies indicated that NIR spectroscopy is feasible and promising in the quality control of meat products, the results, especially on meat tenderness predictions, have been inconsistent, partially because NIR spectroscopy measures the overtones of fundamental molecular vibration modes which are often overlapped to yield broad bands that do not provide high resolution information about the biochemical landscape of the meat.…”
Section: Introductionmentioning
confidence: 99%
“…NIR models have predictions rating fair to good for the tenderness of postrigor longissimus muscle in many publications [120,148,156,162], and [157]. Common measurement ranges were 1100-2500 nm and 750-1100 nm.…”
Section: B110 Tendernessmentioning
confidence: 99%
“…Information about sample characteristics, process, and slaughter conditions can be found, for example, in Cozzolino et al [166], Cozzolino et al [146], Cozzolino et al [167], Mitsumoto et al [148] 1991, Swatland [145], and Cozzolino and Murray [150].…”
Section: B115 Other Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…They used textural features and achieved a prediction accuracy of 70.3%. Mitsumoto et al (1991) pioneered the use of spectroscopy for beef tenderness prediction and obtained an accuracy of 68% in predicting tenderness. Subsequently several additional studies reported moderate to promising results in predicting beef tenderness (Hildrum et al, 1994(Hildrum et al, , 1995Rødbotten et al, 2001;Park et al, 1998;Jeyamkondan and Kranzler, 2003;Liu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%